Assessing the economic viability of commercial moringa production for Kenyan small-scale farmers - Waterman, C.; Peterson, A.; Schelle, C.; Vosti, S.A.; McMullin, S. (Emerald Publishing Limited, 2021)
Purpose: Moringa (Moringa oleifera) is a highly nutritious, fast-growing crop that has emerged in Western markets as a “superfood” and as a “smart crop” for income generation potential among small-scale farmers. As such, moringa has been widely promoted by agricultural development practitioners in low-income countries and by emerging businesses aimed at achieving nutritional and social impact. However, the intrinsic nutritional and agronomic strengths of moringa are not enough to warrant its widespread promotion without first evaluating its economic potential to farmers. Design/methodology/approach: A Land Use System (LUS) analysis modeling tool was employed to test the economic performance of two sets of moringa production practices in Kenya. Data were collected during in-depth interviews and field visits with farmers in Meru that supply a local market, and in Shimba Hills that supply an organic export market. Findings: Results suggest that current production practices over an 12-years assessment period generate a Net Present Value (NPV) of US$8,049 [ha-1] in Meru and a negative NPV of US$697 [ha-1] in Shimba Hills; with average daily returns to family labor of these two production systems of roughly 1.6 times and 0.13 times the prevailing local wage rate, respectively. These differences were attributed to a higher farmgate prices and greater yields in Meru. The analysis tool was then used to predict the effects of changes in farming practices, e.g. if farmers in Meru switched to intensive bed cultivation NPV is estimated to increase by ∼650%. Research limitations/implications: This study demonstrates the importance of examining the economic performance of agricultural production systems intended to increase the benefits to small-scale farmers. Originality/value: Our study is the first to assess moringa's economic performance within two production systems in Kenya – a local farmers' cooperative in Meru, and a group of farmers contracted by an export company.